Electronic health records are the next frontier for the genetics of substance use disorders - Sanchez-Roige, Sandra (Trends Genet, 2019)
Compared to other psychiatric disorders of similar heritabilities, the progress of substance use disorders (SUD) genetics has been slow. With the growing availability of large-scale biobanks with extensive phenotypes from electronic health records (EHR) and genotypes across millions of individuals, this platform is the next tool to accelerate SUD genetics research.